Daily patient-reported health status assessment improvements with benralizumab for patients with severe, uncontrolled eosinophilic asthma - O’Quinn, Sean (J Asthma Allergy, 2019)
BACKGROUND: Patients with severe, uncontrolled asthma experience debilitating symptoms that result in meaningful reductions to health-related quality of life. Benralizumab is an interleukin-5 receptor alpha–directed cytolytic monoclonal antibody that reduces exacerbations and improves asthma symptoms for patients with severe, uncontrolled eosinophilic asthma. OBJECTIVE: The objective of this study was to evaluate improvements in daily asthma-related health status outcomes following treatment with benralizumab. METHODS: Pooled results from the SIROCCO (NCT01928771) and CALIMA (NCT01914757) Phase III studies were analyzed. Patients aged 12–75 years with severe, uncontrolled asthma, and blood eosinophil counts (BEC) ≥300 and ≥150 cells/µL were evaluated. Patients received subcutaneous benralizumab 30 mg every 4 weeks (Q4W) or every 8 weeks (Q8W, first three doses Q4W) or placebo and completed a daily diary reporting rescue medication use, night-time awakening requiring rescue medication use, perceived tiredness, and asthma-related activity impairment. Outcome measures were compared across treatment arms from baseline to end of treatment (EOT) using a mixed-effect model for repeated measures analyses. RESULTS: Patients with BEC ≥300 cells/µL receiving benralizumab Q8W had greater improvements in all patient-reported outcomes at EOT relative to baseline than patients receiving placebo (all nominal P≤0.013). Effects were reported as early as 3 days following the initial dose and sustained throughout treatment for daily and night-time rescue medication use and night-time awakenings requiring rescue medication. For patients with BEC ≥300 and ≥150 cells/ µL, sustained improvements in activity impairment items (all nominal P<0.05) were achieved with benralizumab Q8W at week 2. CONCLUSION: Benralizumab produces sustained reductions by as early as 3 days in rescue medication use and activity impairment for patients with severe, uncontrolled eosinophilic asthma.